The importance of carbohydrate intake for high-performance athletes in endurance exercises (Research, Society and Development, 2025)
Adequate nutrition is essential for endurance athletes, directly influencing performance, recovery, and muscle and liver glycogen stores. This study aimed to demonstrate the importance of proper carbohydrate (CHO) intake for high-performance athletes during endurance training and competitions, addressing effective nutritional strategies, physiological adaptations, and specific recommendations to optimize performance and recovery. Based on articles published between 2014 and 2024 in SCIELO, PubMed, BIREME, and EBSCO, the review highlighted strategies such as combining different types of CHO to maximize absorption and exercise intensity adaptation. Results showed that a daily intake of 7-10 g/kg of CHO is required to replenish glycogen stores within 24 hours, while consuming 60-90 g/h during exercise improves energy oxidation and reduces fatigue. Gastrointestinal training also proved relevant, enhancing CHO tolerance and absorption while minimizing discomfort and optimizing performance. Inadequate nutritional planning was associated with energy deficits and insufficient muscle recovery. The study concluded that personalized nutrition, with specialized guidance, is crucial for maximizing results, preventing injuries, and accelerating recovery. Additionally, further research is needed to refine high-performance nutritional strategies. In summary, adequate CHO intake, combined with strategies like gastrointestinal training, is key to success in endurance sports, emphasizing the importance of individualized nutritional interventions for elite athletes.